2013
DOI: 10.1002/nbm.2972
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic imaging of acute and chronic infarction in the perfused rat heart using hyperpolarised [1‐13C]pyruvate

Abstract: Hyperpolarised 13 C MRI can be used to generate metabolic images of the heart in vivo. However, there have been no similar studies performed in the isolated perfused heart. Therefore, the aim of this study was to develop a method for the creation of 13 C metabolite maps of the perfused rat heart and to demonstrate the technique in a study of acute and chronic myocardial infarction. Male Wistar rat hearts were isolated, perfused and imaged before and after occlusion of the left anterior descending (LAD) coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 50 publications
2
37
1
Order By: Relevance
“…We found that the 13 C Bic/Lac ratio in the IRI kidneys was approximately 51% lower at day 7 when compared with baseline, and the 13 C Bic/Lac ratio was significantly lower in the IRI kidneys when compared with that in the contralateral sham‐operated kidneys at day 7. The Bic/Lac ratio has been suggested to serve as a sensitive metric for the opposing changes in the conversion of Pyr to Bic and Lac . In addition, as both Bic and Lac are produced from Pyr, the Bic/Lac ratio can be used to account for changes in perfusion between baseline and following IRI .…”
Section: Discussionmentioning
confidence: 99%
“…We found that the 13 C Bic/Lac ratio in the IRI kidneys was approximately 51% lower at day 7 when compared with baseline, and the 13 C Bic/Lac ratio was significantly lower in the IRI kidneys when compared with that in the contralateral sham‐operated kidneys at day 7. The Bic/Lac ratio has been suggested to serve as a sensitive metric for the opposing changes in the conversion of Pyr to Bic and Lac . In addition, as both Bic and Lac are produced from Pyr, the Bic/Lac ratio can be used to account for changes in perfusion between baseline and following IRI .…”
Section: Discussionmentioning
confidence: 99%
“…This generated a KH buffer with a final substrate concentration of 10mM glucose and 4mM hyperpolarized [1‐ 13 C]acetoacetate or [1‐ 13 C]β‐hydroxybutyrate. The supply to the perfused heart was subsequently switched to the hyperpolarized solution and a 13 C pulse–acquire experiment was immediately started (TR = 1 s; hard pulse; sweep width, 180 ppm; 4096 complex points) with a 30° flip angle chosen as a compromise between the signal‐to‐noise ratio (SNR), intracellular metabolite signals and magnetization depletion, as discussed elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, cardiac conditions, such as ischemic disease, may have regional myocardial involvement, which will only be adequately assessed by generating 2D or 3D metabolic maps of 13 C-MRS imaging in pigs. Ball et al 14 demonstrated the feasibility of 13 C-MRS imaging in the isolated rat heart, but the technological requirements are a long way from allowing translation to in vivo rat studies. An important aspect is the translational value of the technological improvements of 13 C-MRS (in pigs studies), particularly in coil design, radiofrequency sequence optimization, and 13 C-kinetic modeling.…”
Section: Aquaro and Menichetti Hyperpolarized 13c-magnetic Resonance mentioning
confidence: 99%